1999
DOI: 10.1111/j.1447-0756.1999.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myometrial Invasion at the Invasion Site of an Endometrial Carcinoma by Ultrasonography Along with an Intrauterine Catheter

Abstract: It is of value to use 6-mm as the criterion for the thickness of the intact myometrium at the estimated tumor-origin site in connection with TVU with the use of a catheter for preoperatively assessing half myometrial invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They showed that, in cases with a correctly estimated original site, the sensitivity, specificity and accuracy of TVS using a catheter were respectively 1.00, 0.67 and 0.86 for myometrial invasion of !½, and 0.67, 1.00 and 0.86 for myometrial invasion of 6½. Their results seems to be better, but were based only on 19 patients, thereby warranting further investigation [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that, in cases with a correctly estimated original site, the sensitivity, specificity and accuracy of TVS using a catheter were respectively 1.00, 0.67 and 0.86 for myometrial invasion of !½, and 0.67, 1.00 and 0.86 for myometrial invasion of 6½. Their results seems to be better, but were based only on 19 patients, thereby warranting further investigation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Perdomo et al [15] used an intrauterine silicon catheter to enhance the diagnostic ability of TVS. They showed that, in cases with a correctly estimated original site, the sensitivity, specificity and accuracy of TVS using a catheter were respectively 1.00, 0.67 and 0.86 for myometrial invasion of !½, and 0.67, 1.00 and 0.86 for myometrial invasion of 6½.…”
Section: Discussionmentioning
confidence: 99%